ASSAINISSEMENT ECOLOGIQUE: ENTRE LOGIQUE DES ACTEURS ET ADOPTION D’UNE INNOVATION - Brou Ahossi Nicolas (European Scientific Journal, ESJ, 2015)
Clean up the environment by a rural innovation is an activity that requires both a technological expertise and support of the people The study conducted in Petit Badien (southern Côte d'Ivoire), has shown that it is possible to overcome socio-cultural resistance due to ecological sanitation (EcoSan).The methodology was based on the realization of special latrines that promote the separation of urine from the faeces, public urinals, the introduction into the cans of households called " Bidur " to collect the urine and the use of urine and sanitized faeces to fertilize two experimental fields (yam and cassava). Awareness-raising activities were also conducted. To measure the change in behavior of populations, different socio-anthropological studies were conducted at each major project time: the beginning of the project, at the time of construction of the works and harvesting of agricultural products. The results show that doubt and mistrust towards the use of project implementation beginning in urine population gradually gave way to their accession to the effective use of urine as fertilizer. Women showing interest in cassava production from fields fertilized with urine by accepting to cook the harvested tubers. People have consumed the product of the harvest in various forms (meal). Students not defecate near the primary school and teachers volunteer to popularize the EcoSan concept in their regions of origin.